Current practice patterns in pancreatic surgery: results of a multi-institutional analysis of seven large surgical departments in Germany with 1454 pancreatic head resections, 1999 to 2004 (German Advanced Surgical Treatment Study Group) - Makowiec, Frank; Post, Stefan; Saeger, Hans-Detlev; Senninger, Norbert; Becker, Heinz; Betzler, Michael; Buhr, Heinz J.; Hopt, Ulrich T. (Journal of gastrointestinal surgery, 2005)
Despite decreasing mortality rates, morbidity is still high after pancreatic head resection. Comparative data in the United States and Europe show a relationship between hospital volume and mortality. Treatment strategies vary frequently, partially because of the lack of evidence-based data. We performed a multi-institutional analysis in Germany evaluating current numbers, indications, techniques, and complication rates of pancreatic head resection. Questionnaires were completed by seven high-volume surgical departments regarding quantitative and qualitative aspects of pancreatic head resections in the period from 1999 to 2004 (five prospective and two retrospective institutional databases). A total of 1454 pancreatic head resections (944 for malignancy) were reported. Mean annual hospital volume ranged from 14 to 52 (10 to 43 in malignancy). Mortality was between 1.1% and 4.8%, morbidity was between 24% and 46%, and pancreatic leakage was between 9% and 20%. In malignant disease, all centers perform standard lymphadenectomy and regard arterial infiltration as a contraindication for resection. However, the rate of portal vein resection varied from 0% to 28%. No consensus is seen on the type of surgery for malignancy and chronic pancreatitis. After resection for pancreatic cancer less than one fourth of the patients receive adjuvant therapy. The results of our analysis in Germany confirm that pancreatic head resection can be performed with low mortality in specialized units. Variations in indications, operative technique, and perioperative care may demonstrate the lack of evidence-based data and/or personal and institutional experience. The low number of patients receiving adjuvant therapy after resection of pancreatic cancer suggests that more efforts must be made to establish novel adjuvant therapies under randomized study conditions.